REAERCH IN CONSUMER PURCHASE MOTIVATION AND CONSUMER BEHAVIOR OF CHINESE LUXURY MARKET - Peng, Can (2012)
This report provides the profiling the Chinese consumer toward purchasing luxury brands form the perceptions of luxury values and motivations toward luxury. The literature review presents a conceptual model of luxury consumption and examined by hypothesis the relationship of personal value, motivations and consumer behaviour on purchasing luxury brand with regarding to their response to luxury consumption. The questionnaire survey was conducted by email and telephones to collect data and over 100 people were requested to answer the survey to carry out the analysis. More than 70 responses were received. To carry out the analysis exactly 70 respondents’ data was used. The statistical analysis was carried by the IBM software tool called SPSS. This tool has been an important tool helping out at every step of analysis. There are three aspects to analyse the consumer purchasing behaviour. The first part is personal value factors which are segmented into to two clusters, first being internal value factor and second external value factor. The second part is interpersonal motivation which influence more than personal motivations toward luxury consumption. The third part is the relationship of personal value, motivation and behaviour based on purchasing luxury brands and counterfeit products. All the three aspects are correlated and the factor influencing the most for luxury purchasing is the quality factor. The study of consumer behaviour is an important aspect for luxury brand, this research in focused on achieving such a target. The research can give an idea about the Chinese perception about luxury brands and counterfeit products. The main aim was to understand their behaviour and motivation which is achieved in the research.